The potential of waqf in activating idle agricultural land - Muhammad Hakimi Mohd Shafiai,; Mohammed Rizki Moi,; Riayati Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2015)
This paper attempts to analyse the possibility of collaboration of waqf in agricultural land development realizing the farmers’ financial problems in developing their land. The early Muslims made contracts among themselves as individuals without banks, self-regulated by their adherence to shariah. However, it can be argued that these days the money lenders or banking institutions have established themselves as the most easily accessible source of financing. Therefore, the fruits of transaction in the real world depend very much on the religious sincerity of the bankers. Unfortunately, the bank is an institution, not an individual, and is unlikely to favour transactions involving mutual trust and risk. Accordingly, it seems that another practical way to ensure the implementation of Islamic instruments that would really help rural economies like agriculture in developing countries would be to establish Islamic trusts (waqf) specifically designed for the purpose. It is believed, eventually, that appropriate charitable institutions could be approached to create, administer and develop trust property to be utilized to cater specific needs of Islamic societies.